Agent-Operational Activities of Soviet Security Services in A Protestant Environment (1945-1953) - Tryhub, Oleksandr Petrovyč (Occasional papers on religion in Eastern Europe, 2021)
The place and role of Soviet security services in the development of two Protestant movements, Pentecostals and Adventists-Reformists, are examined in the paper, based on previously classified documents of the Committee for State Security of the USSR. The development of these confessions in the late Stalinist post-war period of 1945-1953 is analyzed. The main intention of the Soviet state security services among Pentecostals was to dissolve them through integration with the Baptist congregations. The August Agreement on integrating Evangelical Christians-Baptists and Christians of Evangelical Faith (Pentecostals), carefully prepared by the special services, was not fully concluded. Most of the Pentecostal congregations did not support the integration and continued their independent existence in the underground. Their radical position led to the intensification of the repressive machinery of the Soviet state. In order to expose the underground Pentecostal congregations, the state security services used a full range of tools and tactics-recruiting agents, conducting special operations, arrests, and deportations, etc. Despite massive repression, Pentecostals retained their congregations and believers. Soviet security services also adopted an aggressive attitude towards Adventists-Reformists. The latter could not agree with a number of Soviet demands, one of which was compulsory military service. The primary way of struggle with Adventists-Reformists was the use of repression to suppress their religious movement. Using an extensive network of agents, state security services were able to identify the underground Adventists-Reformists congregations and, after well-planned operations, carried out group arrests. Those arrested were convicted in closed court hearings and sentenced to lengthy terms of imprisonment. Thus, despite the commitment to religious freedom declared by Stalin under pressure from the allies, Bolshevik repressive practices concerning the religious organizations in the 1920s and 1930s persisted. Although the anti-religious strategy of the communist party state toward Protestant movements in the post-war Stalinist era did not change, it gained a new breath and more sophisticated mechanisms of implementation through state security services.